1964
DOI: 10.4319/lo.1964.9.1.0103
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on the Growth of an Obligate Psychrophilic Marine Bacterium 12

Abstract: A marine vibrio, designated as MP‐1, was isolated from the North Pacific Ocean and was found to be an obligate psychrophile. Growth was obtained from ‒1C (lowest tested) to 20C with optimal growth at 15–16C. The growth rate at 15C was found to be rapid under maximal aeration. Viability of the bacterium was destroyed by heating at 28.8C for 6.25 hr, and reversible damage occurred at 28.8C in 1.25 hr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1966
1966
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Thus the unidentified low-tem~erature basidiomvcetes and several species of T y p h u l a referred t o above have very low maximuin growth temperatures. Similar characteristics are exhibited by some psychrophilic bacteria and yeasts (5,13,18,23).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Thus the unidentified low-tem~erature basidiomvcetes and several species of T y p h u l a referred t o above have very low maximuin growth temperatures. Similar characteristics are exhibited by some psychrophilic bacteria and yeasts (5,13,18,23).…”
mentioning
confidence: 57%
“…However, since then, there have been several reports of yeasts and bacteria which fit the more restrictive definition (1,8,18,23). Baxter and Gibbons (1) have suggested that this definition be retained for psychrophiles while the other group of microorganisms that are able t o grow a t low temperatures be regarded as merely cold tolerant.…”
Section: Discussionmentioning
confidence: 98%
“…It was described by Morita and Haight (1964) as being a "gram-negative, oxidase-positive, motile, pleomorphic vibrio" which had the growth-temperature characteristics of an obligate psychrophile as defined by Stokes (1963). A more comprehensive taxonomic description of this organism, including both quantitative and qualitative data, was given by Colwell and Morita (1964).…”
Section: Organismmentioning
confidence: 99%
“…They established a double mediu~ll technique in which injured cells grew on one medium but not on the other, and used this technique to study thermal injury and repair in mesophiles (Iandolo and Ordal 1966;Tomlins and Ordal 1971;Clark et al 1968). Psychrophilic bacteria sustain thermal injuries at relatively low temperature as compared to mesophiles (Morita and Haight 1964). Several types of thermal injury have been reported for the psychrophilic marine bacterium, Vibrio marin~rs, including leakage (Haight and Morita 1966), cell lysis (Kenis and Morita 1968), and 1Received July 25, 1972.…”
Section: Introductionmentioning
confidence: 99%
“…The GenBanUEMBUDDBJ accession number for the 165 rRNA sequence reported in this paper is AB002630 ~~ 00827 0 1998 IUMS several strains have been identified at the species level (Bowman et al, 1997a, b;D'aoust & Kunshner, 1972;Deming et al, 1988;Gounot, 1976;Irgens et al, 1996;Morita & Haight, 1964;Pacha, 1968).…”
Section: Introductionmentioning
confidence: 99%